Problems of delayed birth: the features of fertility in older reproductive age women and their correction methods - І. А. Жабченко; О. Р. Сюдмак (Publishing House TRILIST, 2019)
To date, there has been a significant shift in the age structure of pregnant women in developed countries towards an increasing the proportion of older reproductive women (over 35 years). First of all, it is caused by social trends and successes in the development of reproductive medicine, which has both positive and negative consequences. 35+ women are at increased risk of blood pressure and diabetes, first discovered during pregnancy; the risk of having a baby with chromosomal abnormalities increases with age (the most common is Down syndrome); increases the frequency of miscarriages, ectopic pregnancy, placental presentation, stillbirths, births of children with low body weight and asphyxia, delivery by caesarean section. The article presents up-to-date data on the features of the ovarian reserve, menstrual function and pregnancy onset in late reproductive women. The main risk factors that can prevent the onset of the desired pregnancy in this contingent of women and its normal course, and can cause early reproductive losses are described. The role of nutritional deficits, psychological and physical stressors, infectious component, abortive history, surgical interventions and chronic endometritis that are causes of infertility in women aged 35+ were determined. Given the identified risk factors the main directions of infertility causes correction and principles of pregravid preparation in women with reproductive disorders, which are recommended to be implemented in conjunction with specialized specialists (family doctor, endocrinologist, cardiologist, and neurologist) are identified. Among the main measures at the pregravid stage is correction of hormonal relations in a woman's body and endometrium state (normalization of the menstrual cycle with provision of its two-phase, correction of luteal phase insufficiency for ovulation), treatment of chronic endometritis, folate supplementation with taking into account hypoproteremia, weight loss, correction of hypertensive disorders, psychological support for married couples